PENGARUH LITERASI PASAR MODAL DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN BERINVESTASI MAHASISWA - Fikri, Muhammad Khaerul; Ramadani, Lalu Ahmad; Reza, Muhammad Helmy; Gemilang, Sabrang Gilang (Universitas Islam Negeri Mataram, 2024)
Capital market literacy is very important, because it makes it easier for students to make investment decisions. Risk perception is also a student factor in determining investment decisions, because the lower the risk, the higher it is in determining investment decisions and vice versa. The observation aims to determine the influence of capital market literacy and risk perception on students' investment decisions. This type of research is a quantitative approach. The data analysis method uses multiple linear regression analysis. The population and sample used were all members and administrators of the Mataram State Islamic University Capital Markets Study Group for 2022-2023, a total of 125 people using a saturated sampling technique. The research results show that capital market literacy influences investment decisions with the results of the hypothesis test (t test) (2,657 > 1,979) with a significance value (0.009 < 0.05). Risk perception influences investment decisions with the t test results (5,238 > 1,979) with a significance value (0.000 < 0.05). Meanwhile, capital market literacy and risk perception influence investment decisions simultaneously with the R2 test result (coefficient of determination) obtained at 0.263. This shows that investment decisions are influenced by Capital Market Literacy.